Prototype Smarthome Berbasis Internet of Things (IoT) - Yus Jayusman; Linda Apriyanti; Rizky Saparuly (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2023)
The development of technology is currently increasing very rapidly and is felt in the industrial world and society, one of which is the use of smart home technology, at this time many electrical devices are integrated with computers, this is certainly very useful for human work in operating electrical devices. The purpose of this smart home research is to control electrical and lighting devices in a system that aims to use electrical energy in a building effectively and efficiently. In this study, a smart home system model that works in a controlled manner based on the Internet of Things (IoT) was designed using Arduino and ESP8266 microcontrollers and the prototype method. A prototype system is built and can be controlled remotely using theFirebase Realtime Database. From this it can be concluded that smart homes can control household appliances such as fans, televisions and lights and can be controlled remotely by the user by giving commands through the smart home. Application and connect to the microcontroller to operate and control household appliances to reduce the consumption of electrical energy when the user forgets to turn off household appliances.